Architectural graphics - Ching, Francis D. K. 1943- (John Wiley & Sons, Inc., 2015)
This guide offers an introduction to using graphic tools and drafting conventions to translate architectural ideas into effective visual presentations, using drawings to illustrate the topic effectively. This updated edition includes new information on orthographic projection in relation to 3D models, and revised explanations of line weights, scale and dimensioning, and perspective drawing to clarify some of the most difficult concepts. New examples of modern furniture, APA facilities, and presentation layout provide more up-to-date visuals, and the Reference Center features all new animations, videos, and practice exercises.